Virtual course: STEM/STEAM education, conception and implementation. Experiences of its execution with Costa Rican teachers - López Gamboa, Marco Vinicio (Innovaciones Educativas, 2021)
The experiences are presented during a virtual course on STEM/STEAM education, addressed to teachers and administrative officials from different educational contexts, contents such as models and steps for their implementation were developed. Likewise, aspects such as the virtual environment used for its development and its respective interface stand out, as well as pedagogical mediation activities used, as well as their evaluation. It also shows part of the products made by the participants of the course, which highlight limitations and approaches, as well as designs of learning environments for the implementation of STEM/STEAM education in their corresponding educational contexts. The above, based on the investigation when implementing the virtual course, since the main purpose of this experience was to provide tools and considerations for the implementation of this type of education. Finally, highlight the limitations and approaches proposed by the participants, as well as the different proposals for STEM/STEAM education implementation projects, in which the scope, objectives, methodologies and their different forms of evaluation stand out.